INTERPRETATION OF THE VERSE OF INHERITANCE FROM MUHAMMAD SYAHRUR'S PERSPECTIVE (Analysis of Surah An-Nisa Verse 11 in the Context of Gender Justice) - Shihab Wicaksono (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2025)
This study examines the challenges of interpreting Islamic inheritance law, particularly Surah An-Nisa verse 11, amidst the demands of modern gender justice. The classical interpretation that considers the 2:1 proportion (male:female) as an absolute provision is considered no longer relevant due to the transformation of women's roles, who are now also active as the backbone of the economy. To respond to this dilemma, this thesis analyzes the perspective of the contemporary Muslim thinker, Muhammad Syahrur. Syahrur interprets the inheritance verses using the concepts of al-hadd al-adna (minimal limit) and al-hadd al-a'la (maximum limit). According to Syahrur, the 2:1 provision is the minimum limit (33.33%) that women must receive, allowing society to provide more, even equal inheritance rights, if in accordance with the principles of justice and welfare. Conversely, 2:1 is also the maximum limit (66.67%) for men. This dynamic approach positions the Quranic text as an adaptive ethical guide, providing a coherent solution between the authority of revelation and the needs of contemporary gender justice.